Impact of Feed-the-Future Program on Malnutrition among Children in the Northern Region of Ghana - Anane, A.E. (University Of Ghana, 2020)
Introduction: Malnutrition among children under-five years old is still a major challenge in most developing countries. Efforts geared towards its prevention or reduction should be given the needed attention. Ghana is one of the 30 countries benefiting from the U.S. government Feed the Future (FTF) initiative in fighting global poverty and hunger. The fundamental aim of developmental agencies, governments, and donors globally, is to ‘make a difference’ in the lives and wellbeing of people and society. The need to ensure that resources are used efficiently and effectively becomes imperative as they tend to establish cause and effect of interventions. Objectives: The objective of the study was to evaluate the impact of the FTF program towards the reduction in malnutrition (underweight, stunting, and wasting) in children under-five years old in the Northern Region of Ghana. Methods: Secondary data from the MESTSS PBS 2012 and 2015 were obtained and used for the analysis. The data was imported into Stata version 15.0 for analysis. Logistic regression was done to find correlates of malnutrition. Difference-in-difference estimator model was used to establish the impact of the FTF program in the reduction of malnutrition. Results: For the effect of FTF program, underweight and stunting increased by 0.5 percent (p-value=0.803) and 0.1 percent (p-value=0.988) respectively, whilst there was -0.3 percent (p-value=0.868) reduction in wasting after adjusting for other covariates. Conclusion: Although there was a -0.3 percent reduction in wasting after adjusting for covariates, the change was not statistically significant (p-value=0.868). Hence at a significance level of 5 percent, there was not enough statistical evidence to conclude that the FTF program caused the reduction in wasting at midline. The results of this evaluation would provide evidence to inform evaluation research, and would provide the implementation teams and stakeholders the opportunity to review and strengthen the monitoring and evaluation activities in order to meet the set objectives. Key Words: Impact Evaluation, Malnutrition, Underweight, Stunted, Wasted, Difference-In-Difference
MSc. Public Health Monitoring and Evaluation
Keywords: Impact Evaluation; Malnutrition; Underweight; Malnutrition; Northern Region; Ghana